Positive electrode active material for secondary battery, preparation method thereof, and lithium secondary battery comprising the positive electrode active material
By using lithium composite transition metal oxides with high nickel content in lithium secondary batteries and heat treatment to form a coating layer, the problems of lithium by-product residue and initial resistance increase are solved, and the stability and life characteristics of the battery are improved.
Patent Information
- Application Number
- CN202080030032.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-05-13
- Filing Date
- 2020-05-12
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2040-05-12
AI Technical Summary
Ni-rich positive electrode active material in lithium secondary batteries has reduced structural and chemical stability due to high nickel content, and the residual amount of lithium by-products on the surface increases, resulting in a decrease in battery life and stability. The initial resistance after the washing process increases, affecting the Battery performance.
The lithium composite transition metal oxide containing more than 70 mol% of nickel was used, and heat treatment was carried out at above 600°C by mixing with fluorine polymer and metal coating source to form a coating layer, reducing the residual amount of lithium by-products and improving the surface Defect, reduces initial resistance.
It realizes the reduction of lithium by-product residue under high nickel content, improves battery stability and life characteristics, reduces the initial resistance increase rate, and improves the overall performance of the battery.
Smart Images

Figure CN113711389B_ABST
Abstract
Description
Technical Field
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to Korean Patent Application No. 10-2019-0055799, filed on May 13, 2019, the disclosure of which is incorporated herein by reference. Technical Field
[0004] The present invention relates to a positive electrode active material for a secondary battery, a preparation method thereof and a lithium secondary battery comprising the positive electrode active material. Background Art
[0005] Recently, with the rapid popularization of electronic devices such as mobile phones, notebook computers and electric vehicles using batteries, the demand for secondary batteries with relatively high capacity, small size and light weight has increased dramatically. In particular, because lithium secondary batteries are light in weight and have high energy density, lithium secondary batteries have become the focus as driving power sources for portable devices. Therefore, research and development attempts have been actively carried out to improve the performance of lithium secondary batteries.
[0006] In a lithium secondary battery in which an organic electrolyte or a polymer electrolyte is filled between a positive electrode and a negative electrode (the positive electrode and the negative electrode are respectively formed of active materials capable of inserting and deinserting lithium ions), electric energy is generated by oxidation and reduction reactions when lithium ions are inserted into or deinserted from the positive electrode and the negative electrode.
[0007] As the positive electrode active material of lithium secondary batteries, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2 or LiMn2O4, etc.) or lithium iron phosphate compound (LiFePO4) has been used. In addition, as a method of improving low thermal stability while maintaining the excellent reversible capacity of LiNiO2, lithium composite metal oxides (hereinafter referred to as "NCM-type lithium transition metal oxides" or "NCA-type lithium transition metal oxides") in which a portion of nickel (Ni) is replaced with cobalt (Co) or manganese (Mn) / aluminum (Al) have been developed.
[0008] Recently, the capacity has been increased by increasing the content of nickel (Ni) in NCM / NCA lithium composite transition metal oxides. However, for Ni-rich positive active materials with high nickel content, structural stability and chemical stability are reduced, and because the residual amount of lithium byproducts in the form of LiOH and Li2CO3 on the surface of the positive active material increases with the increase of nickel content in the positive active material, it causes the generation of gas and swelling phenomenon, thereby reducing the life and stability of the battery. Thus, for Ni-rich positive active materials, a washing process for removing lithium byproducts remaining on the surface of the positive active material is essential. However, there is a limitation that if a washing process for removing lithium byproducts is implemented, the life characteristics are sharply deteriorated due to the surface defects of the positive active material. In particular, if the proportion of the washing solution is increased to improve the removal efficiency of lithium byproducts, the removal of lithium byproducts can be effectively carried out, but because the surface defects of the positive active material increase, the life characteristics are further deteriorated.
[0009] In order to improve the degradation of life characteristics caused by the washing process, H3BO3 or the like is used after washing to perform coating at a relatively low temperature of about 260° C. to about 350° C. However, the Ni-rich positive active material is limited in that the initial resistance increases sharply when H3BO3 or the like is coated.
[0010] Therefore, there is a need to develop a Ni-rich positive electrode active material that has a low residual amount of lithium by-products, ensured stability, and excellent initial resistance characteristics and lifespan characteristics while satisfying high capacity. Summary of the invention
[0011] Technical issues
[0012] One aspect of the present invention provides a method for preparing a positive electrode active material and a positive electrode active material prepared thereby, wherein the method can ensure stability and achieve excellent life characteristics by improving surface defects of the positive electrode active material caused by the washing process while causing a small residual amount of lithium by-products by implementing a washing process in a Ni-rich positive electrode active material containing 70 mol % or more of nickel (Ni) to ensure high capacity, and can also improve the problem of initial resistance increase caused by surface coating of the positive electrode active material.
[0013] Technical Solution
[0014] According to one aspect of the present invention, there is provided a positive electrode active material for a secondary battery, the positive electrode active material for a secondary battery comprising: lithium composite transition metal oxide particles, the lithium composite transition metal oxide particles comprising 70 mol % or more of nickel (Ni) relative to all metals other than lithium; and a coating portion formed on the surface of the lithium composite transition metal oxide particles, wherein the coating portion comprises a compound containing fluorine and at least one selected from aluminum (Al), titanium (Ti), magnesium (Mg), zirconium (Zr), tungsten (W) and strontium (Sr), and the Brunauer-Emmett-Teller (BET) specific surface area is within 0.1 m 2 / g~0.9m 2 / g, and the amount of lithium by-products remaining on the surface of the positive electrode active material is 0.65 wt % or less based on the total weight of the positive electrode active material.
[0015] According to another aspect of the present invention, there is provided a method for preparing a positive electrode active material for a secondary battery, the method comprising the following steps: preparing a lithium composite transition metal oxide, the lithium composite transition metal oxide containing more than 70 mol % of nickel (Ni) relative to all metals other than lithium; washing the lithium composite transition metal oxide; and coating the lithium composite transition metal oxide by mixing the washed lithium composite transition metal oxide with a fluorine-based polymer and a metal coating source and heat treating the washed lithium composite transition metal oxide at a temperature above 600°C, the metal coating source containing at least one metal selected from Al, Ti, Mg, Zr, W and Sr.
[0016] According to another aspect of the present invention, a positive electrode and a lithium secondary battery including the positive electrode active material are provided.
[0017] Beneficial Effects
[0018] According to the present invention, in the high Ni positive electrode active material, by reducing the residual amount of lithium by-products while improving the surface defects of the positive electrode active material caused by the washing process, stability can be ensured and excellent life characteristics can be obtained. In addition, a uniform coating can be formed on the surface of the positive electrode active material, and the problems of initial resistance increase and high resistance increase rate caused by surface coating of the positive electrode active material can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 A graph showing the measurement of initial resistance of lithium secondary batteries prepared by using the positive electrode active materials of Examples and Comparative Examples during 0.2C discharge;
[0020] Figure 2A graph showing the measurement of initial resistance of lithium secondary batteries prepared by using the positive electrode active materials of Examples and Comparative Examples during 2.0C discharge;
[0021] Figure 3 A graph showing the measurement of the capacity retention rate of lithium secondary batteries prepared by using the positive electrode active materials of Examples and Comparative Examples;
[0022] Figure 4 The graph is a graph showing the measured resistance increase rates of lithium secondary batteries prepared by using the positive electrode active materials of Examples and Comparative Examples. DETAILED DESCRIPTION
[0023] Hereinafter, the present invention will be described in more detail to make the present invention more clearly understood. In this case, it should be understood that the words or terms used in the specification and claims should not be interpreted as the meanings defined in the commonly used dictionaries, and it should be further understood that the words or terms should be interpreted as having the meanings consistent with their meanings in the relevant technical field background and technical concepts of the present invention on the basis of the principle that the inventor can appropriately define the meanings of the words or terms to best explain the present invention.
[0024] <Method for preparing positive electrode active material and positive electrode active material>
[0025] The present invention prepares a positive electrode active material for a secondary battery by a method comprising the following steps: preparing a lithium composite transition metal oxide, the lithium composite transition metal oxide containing 70 mol% or more of nickel (Ni) relative to all metals other than lithium; washing the lithium composite transition metal oxide; and coating the lithium composite transition metal oxide by mixing the washed lithium composite transition metal oxide with a fluorine-based polymer and a metal coating source and heat-treating the washed lithium composite transition metal oxide at a temperature of 600° C. or more, the metal coating source containing at least one metal selected from aluminum (Al), titanium (Ti), magnesium (Mg), zirconium (Zr), tungsten (W) and strontium (Sr). Hereinafter, each step of the present invention will be described in more detail.
[0026] First, a lithium composite transition metal oxide containing 70 mol % or more of nickel (Ni) based on all metals except lithium is prepared.
[0027] The lithium composite transition metal oxide used in the present invention may be, for example, an NCM-type lithium composite transition metal oxide comprising nickel (Ni), cobalt (Co) and manganese (Mn), or may be an NCA-type lithium composite transition metal oxide comprising nickel (Ni), cobalt (Co) and aluminum (Al). In addition, the lithium composite transition metal oxide may be a quaternary lithium composite transition metal oxide mainly comprising four components of nickel (Ni), cobalt (Co), manganese (Mn) and aluminum (Al). Compared with NCM / NCA-type positive electrode active materials, quaternary lithium composite transition metal oxides can improve stability and can improve life without deteriorating output characteristics and capacity characteristics.
[0028] The lithium composite transition metal oxide is a Ni-rich lithium composite transition metal oxide containing 70 mol% or more of nickel (Ni) relative to all metals other than lithium, wherein the amount of nickel (Ni) may be preferably 80 mol% or more and may more preferably be 85 mol% or more. Since the amount of nickel (Ni) in the lithium composite transition metal oxide satisfies 70 mol% or more relative to the amount of all metals other than lithium, a high capacity can be ensured.
[0029] Specifically, the lithium composite transition metal oxide may be represented by Formula 1 below.
[0030] [Formula 1]
[0031] Li p Ni 1-(x1+y1+z1) Co x1 M a y1 M b z1 O2
[0032] In formula 1, M a is at least one selected from manganese (Mn) and aluminum (Al), M b is at least one selected from the following elements: zirconium (Zr), boron (B), tungsten (W), magnesium (Mg), cerium (Ce), hafnium (Hf), tantalum (Ta), titanium (Ti), strontium (Sr), barium (Ba), fluorine (F), phosphorus (P), sulfur (S) and lanthanum (La),
[0033] 0.9≤p≤1.1,0≤x1≤0.2,0≤y1≤0.2,0≤z1≤0.1 and 0 <x1+y1+z1≤0.3。
[0034] In the lithium composite transition metal oxide of Formula 1, lithium (Li) can be included in an amount corresponding to p, i.e., 0.9 ≤ p ≤ 1.1. When p is less than 0.9, the capacity may decrease, and when p is greater than 1.1, the preparation of the positive electrode active material may become difficult because the particles are sintered during the sintering process. Considering the balance between the significant improvement effect of the capacity characteristics of the positive electrode active material due to controlling the amount of Li and the sinterability during the preparation of the active material, it is more preferably to include Li in an amount satisfying 1.0 ≤ p ≤ 1.05.
[0035] In the lithium composite transition metal oxide of Formula 1, Ni can be included in an amount corresponding to 1-(x1 + y1 + z1), for example, 0.7 ≤ 1-(x1 + y1 + z1) < 1. If the amount of Ni in the lithium composite transition metal oxide of Formula 1 is 0.7 or more, a high capacity can be achieved because an amount of Ni sufficient to contribute to charge and discharge is ensured. It is more preferably to include Ni in an amount satisfying 0.80 ≤ 1-(x1 + y1 + z1) ≤ 0.99.
[0036] In the lithium composite transition metal oxide of Formula 1, Co can be included in an amount corresponding to x1, i.e., 0 ≤ x1 ≤ 0.2. When the amount of Co in the lithium composite transition metal oxide of Formula 1 is greater than 0.2, there is a problem that the cost may increase. Considering the significant improvement effect of the capacity characteristics due to the inclusion of Co, specifically, Co can be included in an amount satisfying 0.05 < x1 ≤ 0.2.
[0037] In the lithium composite transition metal oxide of Formula 1, M a can be Mn or Al, or can be Mn and Al, and these metal elements can improve the stability of the active material, thereby improving the stability of the battery. Considering the improvement effect of the life characteristics, M can be included in an amount corresponding to y1, i.e., 0 ≤ y1 ≤ 0.2. a If y1 in the lithium composite transition metal oxide of Formula 1 is greater than 0.2, there is a problem that the output characteristics and capacity characteristics of the battery may deteriorate, and specifically, M can be included in an amount satisfying 0.05 ≤ y1 ≤ 0.2. a
[0038] In the lithium composite transition metal oxide of Formula 1, M b can be a doping element included in the crystal structure of the lithium composite transition metal oxide, and M can be included in an amount corresponding to z1, i.e., 0 ≤ z1 ≤ 0.1. b
[0039] The lithium composite transition metal oxide is not limited thereto, but can be prepared, for example, by a method in which a cathode active material precursor containing nickel (Ni) and cobalt (Co) and containing at least one selected from manganese (Mn) and aluminum (Al) is mixed with a lithium-containing raw material and sintered at 600°C to 900°C.
[0040] In this case, the positive electrode active material precursor may be an NCM-based compound containing nickel (Ni), cobalt (Co) and manganese (Mn), or may be an NCA-based compound containing nickel (Ni), cobalt (Co) and aluminum (Al), and may be a quaternary positive electrode active material precursor mainly containing four components of nickel (Ni), cobalt (Co), manganese (Mn) and aluminum (Al). In addition, the positive electrode active material precursor may be a compound containing Mn in addition to nickel (Ni), cobalt (Co), manganese (Mn) and / or aluminum (Al). b The positive electrode active material precursor can be used by purchasing a commercially available positive electrode active material precursor, or can be prepared according to a method for preparing a positive electrode active material precursor known in the art.
[0041] For example, the nickel-cobalt-manganese precursor may be prepared by adding a complexing agent containing ammonium cations and a basic compound to a transition metal solution containing a nickel-containing raw material, a cobalt-containing raw material, and a manganese-containing raw material through a coprecipitation reaction.
[0042] The nickel-containing raw materials may, for example, include nickel-containing acetates, nitrates, sulfates, halides, sulfides, hydroxides, oxides or oxyhydroxides, and may specifically include Ni(OH)2, NiO, NiOOH, NiCO3·2Ni(OH)2·4H2O, NiC2O2·2H2O, Ni(NO3)2·6H2O, NiSO4, NiSO4·6H2O, fatty acid nickel salts, nickel halides or combinations thereof, but the present invention is not limited thereto.
[0043] The cobalt-containing raw material may include cobalt-containing acetates, nitrates, sulfates, halides, sulfides, hydroxides, oxides or oxyhydroxides, and may specifically include Co(OH)2, CoOOH, Co(OCOCH3)2·4H2O, Co(NO3)2·6H2O, Co(SO4)2, Co(SO4)2·7H2O or a combination thereof, but the present invention is not limited thereto.
[0044] The manganese-containing raw materials may, for example, include manganese-containing acetates, nitrates, sulfates, halides, sulfides, hydroxides, oxides, oxyhydroxides or combinations thereof, and may specifically include: manganese oxides such as Mn2O3, MnO2 and Mn3O4; manganese salts such as MnCO3, Mn(NO3)2, MnSO4, manganese acetate, manganese dicarboxylate, manganese citrate and fatty acid manganese salts; manganese oxyhydroxide, manganese chloride or combinations thereof, but the present invention is not limited thereto.
[0045] The transition metal solution can be prepared by adding a nickel-containing raw material, a cobalt-containing raw material and a manganese-containing raw material to a solvent, wherein the solvent is specifically water, or a mixture of water and an organic solvent that can be uniformly mixed with water (such as alcohol, etc.), or the transition metal solution can be prepared by mixing an aqueous solution of a nickel-containing raw material, an aqueous solution of a cobalt-containing raw material and an aqueous solution of a manganese-containing raw material.
[0046] The complexing agent containing ammonium cations can include, for example, NH4OH, (NH4)2SO4, NH4NO3, NH4Cl, CH3COONH4, (NH4)2CO3 or a combination thereof, but the present invention is not limited thereto. The complexing agent containing ammonium cations can be used in the form of an aqueous solution, in which case, as a solvent, a mixture of water or water and an organic solvent (specifically alcohol, etc.) that can be uniformly mixed with water can be used.
[0047] The alkaline compound may include: hydroxides of alkali metals or alkaline earth metals such as NaOH, KOH or Ca(OH)2; hydrates thereof; or combinations thereof. The alkaline compound may also be used in the form of an aqueous solution, in which case water or a mixture of water and an organic solvent (particularly alcohol, etc.) that can be uniformly mixed with water may be used as the solvent.
[0048] The basic compound is added to adjust the pH of the reaction solution, and the basic compound may be added in such an amount that the pH of the metal solution is 11 to 13.
[0049] The coprecipitation reaction can be carried out in an inert atmosphere such as nitrogen or argon at a temperature ranging from 40°C to 70°C.
[0050] Nickel-cobalt-manganese hydroxide particles are formed by the above method and precipitated in the reaction solution. The precipitated nickel-cobalt-manganese hydroxide particles can be separated and dried according to conventional methods to prepare a nickel-cobalt-manganese precursor.
[0051] The cathode active material precursor prepared by the above method may be mixed with a lithium-containing raw material, or the cathode active material precursor may be mixed with a lithium-containing raw material and sintered at 600° C. to 900° C., for example, 600° C. to 800° C. to obtain a lithium composite transition metal oxide.
[0052] As the lithium-containing raw material, lithium-containing sulfate, nitrate, acetate, carbonate, oxalate, citrate, halide, hydroxide or oxyhydroxide can be used, and there is no particular limitation on these materials as long as they can be dissolved in water. Specifically, the lithium source may include Li2CO3, LiNO3, LiNO2, LiOH, LiOH·H2O, LiH, LiF, LiCl, LiBr, LiI, CH3COOLi, Li2O, Li2SO4, CH3COOLi or Li3C6H5O7, and any one of them or a mixture of two or more thereof may be used.
[0053] Next, the lithium mixed transition metal oxide is washed to remove lithium by-products present on the surfaces of the lithium mixed transition metal oxide particles.
[0054] For high-Ni lithium composite transition metal oxides, because the structure is unstable compared to lithium composite transition metal oxides with low nickel content, more lithium by-products such as unreacted lithium hydroxide (LiOH) or lithium carbonate (Li2CO3) are produced in the preparation process. For example, for lithium composite transition metal oxides with a nickel fraction of less than 80 mol%, the amount of lithium by-products after synthesis is in the range of about 0.5 wt% to about 0.6 wt%, but for lithium composite transition metal oxides with a nickel fraction of more than 80 mol%, the amount of lithium by-products after synthesis is as high as about 1 wt%. In the case where a large amount of lithium by-products are present in the positive electrode active material, the lithium by-products react with the electrolyte to produce gas and cause swelling, resulting in a greatly reduced high temperature stability. Therefore, a washing process for removing lithium by-products from lithium composite transition metal oxides containing a high concentration of nickel is essential.
[0055] The washing process can be performed, for example, by adding the lithium composite transition metal oxide to a washing liquid such as distilled water or tap water and stirring. In this case, the temperature of the washing liquid used during washing can be in the range of 1°C to 80°C, for example, 5°C to 50°C, and the washing time can be in the range of 3 minutes to 60 minutes, for example, 5 minutes to 40 minutes. When the washing temperature and the washing time satisfy the above ranges, respectively, the lithium byproduct can be effectively removed.
[0056] The washing process can be performed by mixing the washing liquid and the lithium composite transition metal oxide in a weight ratio of 100:20 to 100:300, preferably 100:50 to 100:200, and more preferably 100:60 to 100:180. When the mixing ratio of the washing liquid to the lithium composite transition metal oxide satisfies the above range, the surface defects of the lithium composite transition metal oxide can be reduced as much as possible while the lithium by-products can be effectively removed.
[0057] Next, the washed lithium composite transition metal oxide is coated by mixing a fluorine-based polymer and a metal coating source containing at least one metal selected from Al, Ti, Mg, Zr, W and Sr and heat-treating the mixture at a temperature of 600° C. or higher.
[0058] In general, in the case where the surface of the lithium composite transition metal oxide particles is coated with a fluorine-based polymer such as polyvinylidene fluoride (PVDF), there are limitations in that the effect of extending the life is limited, the resistance increase rate is increased, and the improvement of thermal stability is limited. However, in the present invention, since the surface of the lithium composite transition metal oxide particles is subjected to a composite coating treatment using a metal coating source containing Al or the like and a fluorine-based polymer, the problems of initial resistance increase and high resistance increase rate are solved.
[0059] For example, the washed lithium composite transition metal oxide may be dried at 80° C. to 140° C., and the washed and dried lithium composite transition metal oxide, the fluorine-based polymer, and the metal coating source may be mixed.
[0060] The fluorine-based polymer may include at least one selected from the following polymers: polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoroethylene copolymer (PVDF-co-HFP), polytetrafluoroethylene (PTFE) and polyperfluoroalkoxy (PFA), and polyvinylidene fluoride (PVDF) may be more preferably used because of its high reactivity with the lithium composite transition metal oxide due to its high bulk density during mixing.
[0061] Based on 100 parts by weight of the lithium composite transition metal oxide, the fluorine-based polymer can be mixed in an amount of 0.03 to 5 parts by weight, preferably 0.05 to 3 parts by weight, and more preferably 0.1 to 2 parts by weight. In the case of mixing the lithium composite transition metal oxide and the fluorine-based polymer within the above range, a more uniform coating can be performed, surface defects caused by washing can be effectively improved, and the surface reaction with the lithium composite transition metal oxide caused by the uniform melting point of the polymer leads to an effect of easy control of the Bruer-Emmett-Teller (BET).
[0062] The metal coating source may include at least one selected from the following substances: Al(OH)3, Al2O3, TiO2, Zr(OH)4, ZrO2, Mg(OH)2, MgO, H2WO4, WO3, Sr(OH)2 and SrO, and may more preferably include Al due to its high reactivity with lithium remaining on the surface. In particular, since the melting point of Al(OH)3 is in the low range of 300°C, similar to the melting point of fluorine-based polymers such as polyvinylidene fluoride (PVDF), the reactivity with lithium remaining on the surface is high, thereby facilitating the formation of a solid solution of Li-F, Al-F or Li-Al-O. In particular, Al(OH)3 is more preferred because it is favorable for reacting with the surface positive electrode material at high temperature. For example, for Al4C3, since its melting point is in the very high range of 2200°C, the reactive surface area is low, and the amount of Al in the total source added is about 75 wt%, which is about 35 wt% higher than the case of Al(OH)3. Assuming that the same amount of Al is coated, it can be considered that because less coating source itself is added, the reaction area between the surface and the coating source is reduced and the reactivity is reduced.
[0063] The metal coating source may be mixed in an amount of 0.01 to 5 parts by weight, preferably 0.03 to 3 parts by weight, and more preferably 0.01 to 1 part by weight, based on 100 parts by weight of the lithium composite transition metal oxide. In the case where the lithium composite transition metal oxide and the metal coating source are mixed within the above range, the degradation of the lifespan may be effectively improved by the reaction of the lithium composite transition metal oxide with the metal coating source.
[0064] In addition, the fluorine-based polymer and the metal coating source may be mixed in a weight ratio of 1:0.01 to 1:5, preferably 1:0.1 to 1:3, and more preferably 1:0.3 to 1:3. When the fluorine-based polymer and the metal coating source are mixed within the above range, while effectively improving surface defects caused by washing, side reactions can be suppressed by reducing BET due to polymer coating.
[0065] Preferably, the coating may be performed by mixing lithium composite transition metal oxide, polyvinylidene fluoride (PVDF) and Al(OH) 3 .
[0066] The coating can be performed by heat treatment at 600°C or more, preferably 600°C to 800°C, and more preferably 700°C to 800°C. In the case where the heat treatment temperature of the coating is lower than 600°C, it is difficult to uniformly coat the fluorine-based polymer, and the surface defects caused by washing cannot be effectively improved. Since the coating is performed by heat treatment at 600°C or more, preferably 600°C to 800°C, and more preferably 700°C to 800°C, stability is ensured by effectively reducing the BET specific surface area that has increased due to washing, and a reduction in the resistance increase rate and excellent life characteristics can be achieved.
[0067] Next, the positive electrode active material for a secondary battery according to the present invention is described.
[0068] The positive electrode active material for a secondary battery of the present invention prepared according to the above method comprises: lithium composite transition metal oxide particles, the lithium composite transition metal oxide particles containing 70 mol% or more of nickel (Ni) relative to all metals other than lithium; and a coating portion formed on the surface of the lithium composite transition metal oxide particles, wherein the coating portion contains a compound containing fluorine and at least one selected from Al, Ti, Mg, Zr, W and Sr, and the BET specific surface area is 0.1 m 2 / g~0.9m 2 / g, and the amount of lithium by-products remaining on the surface of the positive electrode active material is 0.65 wt % or less based on the total weight of the positive electrode active material.
[0069] The lithium composite transition metal oxide is a Ni-rich lithium composite transition metal oxide containing 70 mol% or more of nickel (Ni) relative to all metals other than lithium, wherein the amount of nickel (Ni) may be preferably 80 mol% or more and the amount of nickel (Ni) may be more preferably 85 mol% or more. Since the amount of nickel (Ni) in the lithium composite transition metal oxide satisfies 70 mol% or more relative to all metals other than lithium, a high capacity can be ensured.
[0070] Specifically, the lithium composite transition metal oxide may be represented by Formula 1 below.
[0071] [Formula 1]
[0072] Li p Ni 1-(x1+y1+z1) Co x1 M a y1 M b z1 O2
[0073] In formula 1, M a is at least one selected from Mn and Al, M bis at least one selected from the following elements: Zr, B, W, Mg, Ce, Hf, Ta, Ti, Sr, Ba, F, P, S, and La, 0.9 ≤ p ≤ 1.1, 0 ≤ x1 ≤ 0.2, 0 ≤ y1 ≤ 0.2, 0 ≤ z1 ≤ 0.1 and 0 < x1 + y1 + z1 ≤ 0.3. Since the specific specifications of the lithium composite transition metal oxide represented by Formula 1 are the same as those described in the preparation method, detailed description is omitted.
[0074] The coating part contains a compound containing fluorine and at least one selected from Al, Ti, Mg, Zr, W, and Sr.
[0075] For the positive electrode active material according to the present invention as described above, since the coating part is formed by mixing a fluoropolymer and a metal coating source containing at least one metal selected from Al, Ti, Mg, Zr, W, and Sr after washing and performing heat treatment at 600 °C or higher, preferably 600 °C to 800 °C, and more preferably 700 °C to 800 °C, the residual amount of lithium by-products is significantly less than that of conventional Ni-rich positive electrode active materials, and the BET specific surface area increased due to washing is effectively reduced. Thus, surface defects can be improved, excellent stability can be achieved, and the initial resistance can be reduced.
[0076] The amount of lithium by-products remaining on the surface of the positive electrode active material according to the present invention can satisfy 0.65 wt% or less, preferably 0.60 wt% or less, and more preferably 0.56 wt% or less. Thus, in the case of preparing a secondary battery by using the positive electrode active material according to the present invention, gas generation and swelling phenomena during charging and discharging can be effectively suppressed.
[0077] In addition, the BET specific surface area of the positive electrode active material according to the present invention can be 0.1 m 2 / g to 0.9 m 2 / g, preferably 0.2 m 2 / g to 0.8 m 2 / g and more preferably 0.3 m 2 / g to 0.7 m 2 / g. For the positive electrode active material prepared by the preparation method of the present invention, since the coating part is formed by performing heat treatment at 600 °C or higher, preferably 600 °C to 800 °C, and more preferably 700 °C to 800 °C, the BET specific surface area increased due to washing is effectively reduced. Thus, stability can be ensured and excellent life characteristics can be obtained.
[0078] <Positive Electrode and Secondary Battery>
[0079] According to another embodiment of the present invention, a positive electrode for a lithium secondary battery and a lithium secondary battery including the positive electrode active material are provided.
[0080] Specifically, the positive electrode includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector and including a positive electrode active material.
[0081] In the positive electrode, there is no particular limitation on the positive electrode collector as long as it has conductivity and does not cause adverse chemical changes in the battery, and for example: stainless steel, aluminum, nickel, titanium, roasted carbon; or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. In addition, the thickness of the positive electrode collector can generally be 3 μm to 500 μm, and fine concavoconvexity can be formed on the surface of the collector to improve the adhesion of the positive electrode active material. For example, the positive electrode collector can be used in various shapes such as films, sheets, foils, nets, porous bodies, foams, non-woven fabrics, etc.
[0082] Furthermore, the positive electrode active material layer may further contain a conductive material and a binder in addition to the above-mentioned positive electrode active material.
[0083] In this case, the conductive material is used to provide conductivity to the electrode, wherein any conductive material can be used without particular limitation, as long as it has suitable electronic conductivity and does not cause adverse chemical changes in the battery. Specific examples of conductive materials can be: graphite such as natural graphite or artificial graphite; carbon materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black and carbon fiber; powder or fiber of metals such as copper, nickel, aluminum and silver; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and any one of them or a mixture of two or more thereof can be used. The content of the conductive material is generally 1% to 30% by weight based on the total weight of the positive electrode active material layer.
[0084] In addition, the binder improves the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material and the collector. Specific examples of the binder can be: polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or its various copolymers, and any one of them or a mixture of two or more thereof can be used. Based on the total weight of the positive electrode active material layer, the content of the binder can be 1% to 30% by weight.
[0085] In addition to using the above-mentioned positive electrode active material, the positive electrode can be prepared according to a typical method for preparing a positive electrode. Specifically, a composition for forming a positive electrode active material layer comprising the above-mentioned positive electrode active material and a selective binder and a conductive material is applied to a positive electrode current collector, and then the positive electrode can be prepared by drying and rolling the coated positive electrode current collector. In this case, the type and amount of the positive electrode active material, the binder and the conductive material are the same as those previously described.
[0086] The solvent may be a commonly used solvent in the art. The solvent may include dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), acetone or water, and any one thereof or a mixture of two or more thereof may be used. If the coating thickness and manufacturing yield of the slurry are taken into account, the solvent may dissolve or disperse the positive electrode active material, the conductive material and the binder, and may allow for a viscosity that can provide excellent thickness uniformity during subsequent coating for preparing the positive electrode, then the amount of the solvent used may be sufficient.
[0087] Furthermore, as another method, the positive electrode may be prepared by casting a composition for forming a positive electrode active material layer on a separate support and then laminating a film separated from the support on a positive electrode current collector.
[0088] According to another embodiment of the present invention, an electrochemical device comprising a positive electrode is provided. The electrochemical device may be a battery or a capacitor, for example, a lithium secondary battery.
[0089] The lithium secondary battery specifically comprises a positive electrode, a negative electrode disposed facing the positive electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte, wherein the positive electrode is as described above. In addition, the lithium secondary battery may also selectively comprise a battery container for accommodating an electrode assembly of the positive electrode, the negative electrode and the separator, and a sealing member for sealing the battery container.
[0090] In a lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector.
[0091] There is no particular limitation on the negative electrode collector as long as it has high conductivity and does not cause adverse chemical changes in the battery, and for example: copper; stainless steel; aluminum; nickel; titanium; roasted carbon; copper or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc.; and aluminum-cadmium alloy. In addition, the negative electrode collector may generally have a thickness of 3 μm to 500 μm, and similar to the positive electrode collector, fine concavoconvexities may be formed on the surface of the collector to improve the adhesion of the negative electrode active material. For example, the negative electrode collector may be used in a variety of shapes such as a film, a sheet, a foil, a net, a porous body, a foamed body, a non-woven fabric body, and the like.
[0092] In addition to the negative electrode active material, the negative electrode active material layer also selectively contains a binder and a conductive material. The negative electrode active material layer can be prepared by coating a composition for forming a negative electrode in the form of a slurry containing the negative electrode active material and the selective binder and conductive material on a negative electrode current collector and drying the coated negative electrode current collector, or by casting the composition for forming a negative electrode on a separate support and then laminating a film separated from the support on the negative electrode current collector.
[0093] Compounds that can reversibly intercalate and deintercalate lithium can be used as negative electrode active materials. Specific examples of negative electrode active materials can be: carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber and amorphous carbon; (semi)metallic materials that can form alloys with lithium such as silicon (Si), aluminum (Al), tin (Sn), lead (Pb), zinc (Zn), bismuth (Bi), indium (In), magnesium (Mg), gallium (Ga), cadmium (Cd), Si alloy, Sn alloy or Al alloy; (semi)metallic oxides that can be doped and dedoped with lithium such as SiO α (0<α<2), SnO2, vanadium oxide and lithium vanadium oxide; or a composite material comprising a (semi)metallic material and a carbonaceous material such as a Si-C composite material or a Sn-C composite material, and any one of them or a mixture of two or more thereof can be used. In addition, a metallic lithium film can be used as a negative electrode active material. In addition, both low-crystalline carbon and high-crystalline carbon can be used as carbon materials. Typical examples of low-crystalline carbon may be soft carbon and hard carbon, while typical examples of high-crystalline carbon may be irregular, planar, flaky, spherical or fibrous natural graphite or artificial graphite, condensed graphite, pyrolytic carbon, mesophase pitch-type carbon fibers, mesophase carbon microspheres, mesophase pitch, and high-temperature sintered carbon such as coke derived from petroleum or coal tar pitch.
[0094] Furthermore, the binder and the conductive material may be the same as those previously described in the positive electrode.
[0095] In a lithium secondary battery, the separator separates the negative electrode from the positive electrode and provides a path for the movement of lithium ions, wherein any separator can be used as a separator without particular limitation, as long as it is commonly used in lithium secondary batteries, in particular, a separator having high moisture retention capacity for electrolytes and low resistance to the transfer of electrolyte ions can be used. Specifically, a porous polymer film, such as a porous polymer film prepared from a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer; or a laminated structure having two or more layers thereof. In addition, a typical porous non-woven fabric can be used, such as a non-woven fabric formed of a high melting point glass fiber or a polyethylene terephthalate fiber. In addition, a coated separator comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a separator having a single-layer or multilayer structure can be selectively used.
[0096] In addition, the electrolyte used in the present invention may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte or a molten inorganic electrolyte that can be used in the preparation of a lithium secondary battery, but the present invention is not limited thereto.
[0097] Specifically, the electrolyte may include an organic solvent and a lithium salt.
[0098] Any organic solvent can be used as the organic solvent without particular limitation, as long as it can be used as a medium through which ions participating in the electrochemical reaction of the battery can move. Specifically, the following substances can be used as organic solvents: ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone and ε-caprolactone; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; or carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) and propylene carbonate (PC); alcohol solvents such as ethanol and isopropanol; nitrile such as R-CN (wherein R is a linear, branched or cyclic C2~C20 hydrocarbon group and may contain a double bond, an aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolanes; or cyclopentane sulfone. Among these solvents, carbonate solvents can be used, for example, a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) and a low-viscosity straight-chain carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate, or diethyl carbonate) having high ion conductivity and high dielectric constant that can improve the charge / discharge performance of the battery can be used. In this case, when the cyclic carbonate and the chain carbonate are mixed in a volume ratio of about 1:1 to about 1:9, the performance of the electrolyte can be excellent.
[0099] Lithium salts can be used without particular limitation, as long as they are compounds that can provide lithium ions used in lithium secondary batteries. Specifically, the following substances can be used as lithium salts: LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI or LiB(C2O4)2. Lithium salts can be used in a concentration range of 0.1M to 2.0M. In the case where the concentration of the lithium salt is included in the above range, since the electrolyte can have suitable conductivity and viscosity, the excellent performance of the electrolyte can be obtained, and the lithium ions can be effectively moved.
[0100] In order to improve the life characteristics of the battery, inhibit the reduction of the battery capacity and improve the discharge capacity of the battery, in addition to the electrolyte components, at least one additive may be added to the electrolyte, for example, halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, (condensed) glycol dimethyl ethers, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum trichloride. In this case, the additive may be included in an amount of 0.1 wt % to 5 wt % based on the total weight of the electrolyte.
[0101] As described above, since the lithium secondary battery including the positive electrode active material according to the present invention stably exhibits excellent discharge capacity, output characteristics and capacity retention rate, the lithium secondary battery is suitable for: portable devices such as mobile phones, notebook computers and digital cameras; and electric vehicles such as hybrid electric vehicles (HEV).
[0102] Therefore, according to another embodiment of the present invention, a battery module including the lithium secondary battery as a unit battery and a battery pack including the battery module are provided.
[0103] The battery module or the battery pack may be used as a power source for at least one of the following medium and large-sized devices: a power tool; an electric vehicle, including an electric vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV); or a power storage system.
[0104] Hereinafter, embodiments of the present invention will be described in detail in a manner that can be easily implemented by a person skilled in the art. However, the present invention can be implemented in many different forms and should not be construed as being limited to the embodiments described herein.
[0105] Example 1
[0106] LiOH was added to Ni in an amount such that the molar ratio of Li / metal (Ni, Co, Mn) was 1.05. 0.9 Co 0.05 Mn 0.05 (OH)2 and mixed, and the mixed powder was introduced into an alumina crucible for heat treatment. Thereafter, the mixed powder was sintered at 740°C for 12 hours to prepare a lithium composite transition metal oxide Li 1.05 Ni 0.9 Co 0.05 Mn 0.05 O2(D 50 =4.3μm).
[0107] The distilled water at 25℃ and the lithium composite transition metal oxide Li 1.05 Ni 0.9 Co 0.05 Mn 0.05 O2 was mixed in an amount of 140g and 168g (weight ratio 100:120) for washing and continued for 15 minutes. Thereafter, based on 100 parts by weight of the lithium composite transition metal oxide dried at 130°C, 0.1 parts by weight of polyvinylidene fluoride (PVDF) and 0.09 parts by weight of Al(OH)3 were mixed and heat-treated at 600°C to prepare a positive electrode active material having a coating portion formed on its surface.
[0108] Example 2
[0109] A positive electrode active material was prepared in the same manner as in Example 1, except that MgO was used instead of Al(OH) 3 .
[0110] Example 3
[0111] A positive electrode active material was prepared in the same manner as in Example 1, except that Al4C3 was used instead of Al(OH)3.
[0112] Example 4
[0113] A positive electrode active material was prepared in the same manner as in Example 1, except that the coating portion was formed by performing heat treatment at 700°C instead of 600°C.
[0114] Example 5
[0115] A positive electrode active material was prepared in the same manner as in Example 1, except that the coating portion was formed by performing heat treatment at 800°C instead of 600°C.
[0116] Comparative Example 1
[0117] A positive electrode active material was prepared in the same manner as in Example 1, except that polyvinylidene fluoride (PVDF) and Al(OH) 3 were not mixed with the washed and dried lithium composite transition metal oxide.
[0118] Comparative Example 2
[0119] A positive electrode active material was prepared in the same manner as in Example 1 except that 0.5 parts by weight of H3BO3 was mixed based on 100 parts by weight of the washed and dried lithium composite transition metal oxide and heat-treated at 300°C to form a coating portion on the surface thereof.
[0120] Comparative Example 3
[0121] A positive electrode active material was prepared in the same manner as in Example 1, except that 0.1 parts by weight of polyvinylidene fluoride (PVDF) was mixed based on 100 parts by weight of the washed and dried lithium composite transition metal oxide, and heat-treated to form a coating portion on the surface thereof.
[0122] Comparative Example 4
[0123] A positive electrode active material was prepared in the same manner as in Example 1, except that the coating portion was formed by performing heat treatment at 500°C instead of 600°C.
[0124] [Experimental Example 1: Evaluation of Residual Amount of Lithium Byproducts and BET Specific Surface Area]
[0125] After dispersing 5 g of each positive electrode active material prepared in Examples 1 to 5 and Comparative Examples 1 to 4 in 100 mL of water, the change in pH was measured while the solution was titrated with 0.1 M HCl to obtain a pH titration curve. The residual amount of LiOH and the residual amount of Li2CO3 in various positive electrode active materials were calculated using the pH titration curve, and the sum of these values was evaluated as the total residual amount of lithium byproducts and listed in Table 1 below. The BET specific surface area was measured using a gas adsorption analyzer (BELSORP mini II), and the results are shown in Table 1 below.
[0126] [Table 1]
[0127]
[0128] Referring to Table 1, although the positive electrode active materials prepared in Examples 1 to 5 are Ni-rich positive electrode active materials having Ni of 70 mol % or more, the residual amount of lithium by-products is as low as 0.65 wt % or less. In addition, for the positive electrode active materials prepared in Examples 1, 2, 4, and 5, since the coating portion is formed by heat treatment at a temperature of 600° C. or more, the BET specific surface area is 0.7 m 2 / g or less. However, for Example 3 using Al4C3, the BET specific surface area is slightly higher than that of Examples 1, 2, 4, and 5 due to the reduced reactivity. For Comparative Example 4 in which the coating portion is formed by heat treatment at 500°C, the BET specific surface area is 1.07 m 2 / g, which is about 1.6 times that of Examples 1, 2, 4 and 5.
[0129] [Experimental Example 2: Initial Resistance Evaluation]
[0130] The various positive electrode active materials prepared in Examples 1 to 5 and Comparative Examples 1 to 4, the carbon black conductive material and the PVdF binder were mixed in an N-methylpyrrolidone solvent in a weight ratio of 96:2:2 to prepare a positive electrode material mixture, and one surface of an aluminum current collector was coated with the positive electrode material mixture, dried at 100° C., and then roll-pressed to prepare a positive electrode.
[0131] Lithium metal was used as the negative electrode.
[0132] Various lithium secondary batteries were prepared by preparing an electrode assembly by placing a porous polyethylene separator between the positive electrode and the negative electrode prepared as described above, placing the electrode assembly in a shell, and then injecting an electrolyte into the shell. In this case, the electrolyte was prepared by dissolving 1.0M lithium hexafluorophosphate (LiPF6) in an organic solvent consisting of ethylene carbonate / ethyl methyl carbonate / diethyl carbonate (mixed volume ratio of EC / EMC / DEC = 3 / 4 / 3).
[0133] The various lithium secondary battery half cells prepared as described above were charged to a voltage of 4.25 V at 0.2 C in a constant current / constant voltage (CCCV) mode at 25° C., and discharged at a constant current of 0.2 C to measure the initial resistance at 60 seconds. In addition, various half cells were charged to a voltage of 4.25 V at 0.5 C in a CCCV mode at 25° C., and discharged at a constant current of 2.0 C to measure the initial resistance at 60 seconds. The results are shown in Figure 1 (0.2C discharge) and Figure 2 (2.0C discharge) and in Table 2 below.
[0134] [Table 2]
[0135]
[0136] For the secondary batteries using the positive electrode active materials prepared in Examples 1 to 5, it can be confirmed that the initial resistance is significantly reduced compared to the secondary batteries using the positive electrode active materials of Comparative Examples 1, 2 and 4. In particular, for Comparative Example 2 coated with boron (B), its initial resistance value is relatively higher than that of Examples 1 to 5.
[0137] [Experimental Example 3: Evaluation of Life Characteristics and Resistance Increase Rate]
[0138] Various lithium secondary half-cells prepared in Experimental Example 2 by using various positive electrode active materials prepared in Examples 1 to 5 and Comparative Examples 1 to 4 were charged to a voltage of 4.25V at 0.2C in CCCV mode at 25°C, and discharged in CC mode at 0.2C to measure the initial capacity and resistance at 60 seconds. Thereafter, various half-cells were charged to a voltage of 4.25V at 0.33C in CCCV mode at 45°C, and discharged to a voltage of 2.5V at a constant current of 0.33C to measure the capacity retention rate and resistance increase rate when 30 cycles of charging and discharging were performed. The results are shown in Figure 3 (capacity retention rate), Figure 4 (Resistance increase rate) and in Table 3 below.
[0139] [Table 3]
[0140]
[0141] Refer to Table 3 and Figure 3 and 4 For the secondary batteries using the positive electrode active materials prepared in Examples 1 to 5, it can be confirmed that the capacity retention rate is increased compared with the secondary batteries using the positive electrode active materials of Comparative Examples 1 to 4. For the secondary batteries using the positive electrode active materials prepared in Examples 1 to 5, it can be confirmed that the resistance increase rate is significantly reduced compared with the secondary batteries using the positive electrode active materials of Comparative Examples 1, 2 and 4. In particular, for Examples 1 and 4, the effect of reducing the resistance increase rate is better.
Claims
1. A method for preparing a positive electrode active material for a secondary battery, the method comprising the following steps: preparing a lithium composite transition metal oxide containing 70 mol % or more of nickel relative to all metals other than lithium; washing the lithium composite transition metal oxide; and The lithium composite transition metal oxide is coated by mixing the washed lithium composite transition metal oxide with a fluorine-based polymer and a metal coating source and heat-treating the washed lithium composite transition metal oxide at a temperature of 600° C. or higher, wherein the metal coating source comprises at least one metal selected from the group consisting of Al, Ti, Mg, Zr, W, and Sr, wherein the fluorine-based polymer comprises at least one selected from the following polymers: polyvinylidene fluoride, polyvinylidene fluoride-hexafluoroethylene copolymer, polytetrafluoroethylene and polyperfluoroalkoxy, wherein the metal coating source comprises at least one selected from the group consisting of Al(OH)3, Al2O3, TiO2, Zr(OH)4, ZrO2, Mg(OH)2, MgO, H2WO4, WO3, Sr(OH)2, and SrO, The coating step includes heat treatment at 700°C to 800°C. The BET specific surface area of the positive electrode active material is 0.1 m 2 / g~0.9m 2 / g, and The amount of the lithium by-product remaining on the surface of the positive electrode active material is 0.65 wt % or less based on the total weight of the positive electrode active material.
2. The method according to claim 1, wherein the coating step comprises mixing the washed lithium composite transition metal oxide with polyvinylidene fluoride and Al(OH)3. 3 . The method according to claim 1 , wherein the fluorine-based polymer is mixed in an amount of 0.03 parts by weight to 5 parts by weight based on 100 parts by weight of the lithium composite transition metal oxide. 4 . The method according to claim 1 , wherein the metal coating source is mixed in an amount of 0.01 parts by weight to 5 parts by weight based on 100 parts by weight of the lithium composite transition metal oxide. 5 . The method according to claim 1 , wherein the fluorine-based polymer and the metal coating source are mixed in a weight ratio of 1:0.01 to 1:
5.
6. The method according to claim 1, wherein the lithium composite transition metal oxide is represented by Formula 1: [Formula 1] Li p Ni 1-(x1+y1+z1) Cox1 M a y1 M b z1 O2 in, In formula 1, M a is at least one selected from Mn and Al, M b is at least one selected from the group consisting of Zr, B, W, Mg, Ce, Hf, Ta, Ti, Sr, Ba, F, P, S and La, 0.9≤p≤1.1, 0≤x1≤0.2, 0≤y1≤0.2, 0≤z1≤0.1, and 0 <x1+y1+z1≤0.3。 7. The method according to claim 1, wherein the washing step is performed using a washing solution at 1°C to 80°C and lasts for 3 minutes to 60 minutes. 8 . The method according to claim 1 , wherein the washing step is performed by mixing a washing liquid and the lithium composite transition metal oxide in a weight ratio of 100:20 to 100:300.
